1995
DOI: 10.1002/chem.19950010706
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility in the Reaction of Cyclohexadienyl Radicals with Oxygen in Aqueous Solution

Abstract: Hydroxyl radicals were generated radiolytically and reacted with a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 21 publications
5
69
0
Order By: Relevance
“…2a: an ammoniumyl radical, generated either through N-O bond homolysis or iron-mediated single electron reduction, adds to an arene to generate a putative cationic cyclohexadienyl radical (A). Intermediate A then rearomatizes to the aniline product through one of three pathways: single electron oxidation by iron(III), [43][44][45] aerobic oxidation [46][47][48][49][50] or chain propagation. 51 We identied a hydrogen bond in reagent 1 between one N-H and the triate counterion in the solid state (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2a: an ammoniumyl radical, generated either through N-O bond homolysis or iron-mediated single electron reduction, adds to an arene to generate a putative cationic cyclohexadienyl radical (A). Intermediate A then rearomatizes to the aniline product through one of three pathways: single electron oxidation by iron(III), [43][44][45] aerobic oxidation [46][47][48][49][50] or chain propagation. 51 We identied a hydrogen bond in reagent 1 between one N-H and the triate counterion in the solid state (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It suggested that HO -adduct radical reaction with ozone is dominant, even though O 2 is at least in a 10-fold excess over O 3 in the experimental solutions. It is reasonable because of the very low rate of HO -adduct radicals substituted with eCOOH reacting with O 2 (the second-order rate constant~10 6 M À1 s À1 , Fang et al, 1995). Naumov and von Sonntag (2011) suggested that ozone reacted with HO -adduct radicals by oxygen transfer based on quantum-chemical calculations, and no HO , O 3 $À or O 2 $À /HO 2 is generated like as during ozonation of sulfurcontaining compounds.…”
Section: Possible Reaction Pathwaysmentioning
confidence: 98%
“…The hydroxylation species are further oxidized by O 3 to produce O 3 $À via reaction 3. With regard to the reactivity with oxygen, each of HOadduct radicals may in turn yield two different peroxyl radicals, namely, the 1,3-and 1,4-cyclohexadienyl-type species (Fang et al, 1995), whereby 1,3-cyclohexadienyl-type specie is only the minor component. It has been observed that rapid HO 2 formation can only result from the peroxyl radicals of the cyclohexa-1,3-diene structure but not that for the cyclohexa-1,4-diene structure (Pan et al, 1993).…”
Section: Possible Reaction Pathwaysmentioning
confidence: 99%
“…27). 59,60 Depending on the organic substrate, oxygen addition may be reversible as observed for cyclohexadienyl radicals 61. Peroxyl radicals (ROO • ) can either abstract hydrogen atoms (eq.…”
Section: Chain Processesmentioning
confidence: 99%